On the localization and numerical computation of positive radial solutions for $φ $-Laplace equations in the annulus - Jorge Rodríguez-López; Radu Precup; Calin-Ioan Gheorghiu (Electronic Journal of Qualitative Theory of Differential Equations, 2022)
The paper deals with the existence and localization of positive radial solutions for stationary partial differential equations involving a general $φ $-Laplace operator in the annulus. Three sets of boundary conditions are considered: Dirichlet–Neumann, Neumann–Dirichlet and Dirichlet–Dirichlet. The results are based on the homotopy version of Krasnosel'skii's fixed point theorem and Harnack type inequalities, first established for each one of the boundary conditions. As a consequence, the problem of multiple solutions is solved in a natural way. Numerical experiments confirming the theory, one for each of the three sets of boundary conditions, are performed by using the MATLAB object-oriented package Chebfun.